(3GdCbQGHGPjfs - (3eMeO Hf HgQGe Hf eMeO GdbdGfSj GdSeQbfOj, HOQGdOjf , J (B590 (3g` s ((3eMeO aGVd Hf fXGe GdOjf GdWHjH GdCUagGfj s)
(3ChdgG (B:s
(3eHJhQ GdChd hChd GdehLhO efg(B: (3aj GdCcMGd hGdPQhQGJ JhJjGj cQeGfj hLfc eMQb s
(3BNQgG (B:s
(3hjfGe GdYdjd aj ehVY bO UjQ ajg hQb GdNdGa hhQb GdcQe hGdBS hGdceKQi hGdJaGM s
(3hHGdfSNI HYV UaMGJ HGdaGQSjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B122s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B29 s
Keywords: (3GdWHs